Older Adults in Multifamily Housing: Residential Satisfaction and Intention to Move. (2nd September 2013) - Kwon, Hyun Joo; Beamish, Julia O.
Abstract : This study examined the relationship between residential satisfaction and intention to move among older adults living in multifamily housing based on Morris and Winter's theory of housing adjustment. Residents age 55 years and over living in market‐rate multifamily housing were recruited from a convenience sample ( n  = 431). Exploratory factor analysis, t ‐test, analysis of variance, and multiple regressions were employed. Results revealed that those who were (i) older, healthier, retired, had higher incomes, were owners, living in larger units within newer buildings with elevators located in a city, and paid more monthly housing costs showed higher residential satisfaction; (ii) younger, nonmarried single, and renters were more likely to intend to move; and (iii) satisfied with the unit design and the multifamily community were less likely to intend to move. Findings support the theory of housing adjustment and suggest multifamily housing can be an appealing alternative for seniors.